Mutual accountability in CAADP and agricultural transformation - Benin, Samuel; Ulimwengu, John M.; Matchaya, Greenwell C.; Makombe, Tsitsi; Lorka, Maurice; Vodounhessi, Anselme; Tefera, Wondwosen (Alliance for a Green Revolution in Africa, 2018)
The commitment to mutual accountability to results and action raises a fundamental question about the role of mutual accountability (MA) processes and mechanisms in enhancing the capabilities of governments to implement the vision and strategies that will deliver quick results and foster agricultural growth and transformation on the continent. This chapter addresses this fundamental question and related issues using as background information the inaugural CAADP BR report and the accompanying Africa Agricultural Transformation Scorecard (AATS) that was launched at the 30th ordinary session of the AU assembly in Addis Ababa, Ethiopia, in January 2018 (AUC, 2016).